Apolipoprotein L1 (APOL1) Variants (Vs) a possible link between Heroin-associated Nephropathy (HAN) and HIV-associated Nephropathy (HIVAN) - Lan, Xiqian; Rao, T. K. S.; Chander, Praveen N.; Skorecki, Karl; Singhal, Pravin C. (Frontiers in Microbiology, 2015)
In 1970s, Heroin-associated Nephropathy (HAN), one form of focal and segmental glomerulosclerosis (FSGS), was a predominant cause of End-stage Kidney Disease (ESKD) in African-Americans (AAs). In 1980s, with the surge of Acquired Immune Deficiency Syndrome (AIDS) in AAs, HAN more or less disappeared, and the incidence of Human Immunodeficiency Virus associated Nephropathy (HIVAN) markedly increased. Recent studies in AAs have identified those APOL1 variants (Vs) as a major risk factor for the development and progression of non-diabetic kidney diseases including idiopathic FSGS and hypertension-attributed nephrosclerosis. These observations have also offered partial insights into the mechanisms of development, and higher rate of occurrence of both HAN and HIVAN in AAs. AAs with APOL1Vs develop idiopathic FSGS at 4 fold higher rate compared to European Americans. Similarly, HIV infected AAs with APOL1Vs (if not on antiviral therapy), risk a 50% (10 fold greater) chance of developing HIVAN. It has been suggested that APOL1Vs expression may render podocytes more vulnerable to various types of injury: bacterial, viral and others. However, in addition to genetic variants, additional factors such as persistence of a second hit may determine the nature and severity of glomerular disease. In patients with HAN, heroin or contaminants may have been the offending second insult(s) which caused renal disease in susceptible AA patients. In the 80’s, since heroin-induced second hit was neither consistent nor sustained (depending on drug availability in the street), the disease was masked or replaced HIV infected patients (especially in untreated subjects), by an overwhelming second hit by the virus which was both intense as well as persistent. It appears that APOL1Vs may be one of the links between the disappearance of HAN and emergence of HIVAN in AA patients.